Nothing 'Mere' to It: Reclaiming Subjective Accounts of Normativity of Law. (January 2019) - Swaminathan, S.
If the bindingness of morality was to rest on something as 'subjective' as the non-cognitivist says it does, the grouse goes, and morality itself would come down crashing. Nothing less than an 'objective' (response-independent) source of normativity, it is supposed, could hold morality in orbit. Some of these worries automatically morph into worries about the projectivist model of normativity of law (based on a non-cognitivist meta-ethic) as well: one which understands the authority or normativity of law in terms of subjective attitudes taken towards the law. As well as the stock worries about non-cognitivism, there are some additional ones that the projectivist model brings in its wake that it cannot account for the 'uniform' bindingness of law and that a subjective source of normativity of law based on mental states is unintelligible. This essay makes the case for acquitting the projectivist model of normativity of law from the above charges. But the route to that necessarily leads through first acquitting the non-cognitivist model of moral bindingness from analogous charges.